Fire safety management in heritage buildings: a case study in Malaysia - Salleh, Nurul Hamiruddin; Ahmad, A. Ghafar (2008)

(untitled)
In Malaysia, there are few heritage buildings with an architectural and historical significance that may classified into several categories, namely traditional timber Malay houses, pre-world war shop-houses, colonial office buildings, institutional buildings and religious buildings. Many of them are worthy to be listed as Heritage Buildings or National Heritage buildings under the National Heritage Act 2005 (Act 645). However due to poor fire safety management, many priceless heritage buildings were badly damaged or burnt down by fire e.g. Muzium Rakyat, Melaka (2001), Rumah Pak Ali, Gombak (2003) and Sarawak Club, Kuching (2006).It is widely accepted that fire is one of the greatest threats not only to the building’s occupants but also to the building’s fabric and contents. Nevertheless, in term of fire safety approach, a heritage building requires relatively more sensitive approach compare to a new building; a high standard of fire safety management is required, not only to protect people but as well as to protect historical contents, fabrics and structures of the building. This paper suggests some recommendations to provide a satisfactory level of fire safety management in a heritage building.